Method for manufacturing luminous particle

The surface treatment of strontium aluminate phosphors with organic acids, reduction, and oxidation enhances the afterglow brightness of phosphorescent particles by minimizing non-luminescent phases, resulting in improved initial luminance and stability.

JP2024179682AActive Publication Date: 2024-12-26LTI CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023098713
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-15
Publication Date
2024-12-26
Estimated Expiration
2043-06-15

AI Technical Summary

Technical Problem

Existing methods for producing phosphorescent particles, particularly those doped with strontium aluminate and lanthanoid rare earth elements, suffer from reduced brightness due to the presence of non-luminescent phases on the particle surface, which diminishes their afterglow brightness characteristics.

Method used

A method involving the use of organic acids to treat the surface of strontium aluminate-based phosphors, followed by reduction and oxidation steps to modify the surface, thereby enhancing the luminescent properties and improving afterglow brightness.

Benefits of technology

The process results in phosphorescent particles with enhanced afterglow brightness characteristics, particularly in the initial stages, by reducing non-luminescent phases and promoting efficient charge transitions, and can be further protected with a water-resistant coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024179682000001_ABST
    Figure 2024179682000001_ABST
Patent Text Reader

Abstract

To provide a method for manufacturing a luminous particle with which it is possible to manufacture the luminous particle excellent in afterglow brightness properties.SOLUTION: A method for manufacturing a luminous particle of the present invention includes: preparing a luminous fluorescent body that is a strontium aluminate compound obtained by doping lanthanoid rare earth element as an activator; treating a surface of the luminous fluorescent body with an organic acid; reducing the surface of the luminous fluorescent body after being treated with the organic acid; and oxidizing the surface of the luminous fluorescent body after being subjected to reduction.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing phosphorescent particles. [Background technology]

[0002] Luminous particles absorb light from lighting or the sun, become excited, store the energy of the light, and after the supply of light is cut off, the electronic transition from the excited state to the ground state continues for a certain period of time, that is, they continue to emit light for a certain period of time. Such luminous particles are used in various technologies such as paints, coatings, inks, and plastics, and are applied in various fields such as signs, disaster prevention equipment, interior decoration, lighting, and toys. As one of such phosphorescent particles, a phosphorescent material is known in which strontium aluminate is doped with lanthanoid rare earth elements (especially europium and dysprosium) as an activator. In order to achieve the desired luminous brightness in this phosphorescent material, it is necessary to effectively utilize the phosphorescence that transitions to Eu3+. 7.5 A method for forming the phase is known. However, Sr3Al2DyO 7.5 In this phase, three or more different crystal structures coexist, and different phases exist between these crystal structures. These are areas that are not involved in phosphorescence and are the cause of the decrease in brightness.

[0003] The present applicant has provided a method for producing a phosphorescent phosphor with high initial afterglow brightness by subjecting a phosphorescent particle raw material powder, which is a strontium aluminate compound doped with a lanthanoid rare earth element, to a specified acid / phosphoric acid treatment, washing or neutralizing the powder, and drying the powder (Patent Document 1). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent No. 5967787 [Patent Document 2] Japanese Patent Application Publication No. 11-106678 [Patent Document 3] JP 2008-50548 A Summary of the Invention [Problem to be solved by the invention]

[0005] The phosphorescent particles manufactured by the manufacturing method of Patent Document 1 have satisfied afterglow brightness characteristics in various fields, but in recent years, further improvements have been required.

[0006] The present invention has been made in view of the above circumstances, and has an object to provide a method for producing phosphorescent particles having excellent afterglow brightness characteristics. [Means for solving the problem]

[0007] The method for producing phosphorescent particles of the present invention is characterized by comprising the steps of: preparing a phosphorescent phosphor which is a strontium aluminate compound doped with a lanthanoid rare earth element as an activator; treating the surface of the phosphorescent phosphor with an organic acid; reducing the surface of the phosphorescent phosphor treated with the organic acid; and oxidizing the surface of the reduced phosphorescent phosphor.

[0008] In the method for producing phosphorescent particles of the present invention, the organic acid is preferably an organic acid having a carbon number of 8 or less. Particularly preferred examples include citric acid, formic acid, acetic acid, and lactic acid. The method for producing light-storing particles of the present invention preferably further comprises the step of providing a water-resistant coating on the surface of the oxidized light-storing phosphor. Effect of the Invention

[0009] The method for producing phosphorescent particles of the present invention can obtain phosphorescent particles with excellent afterglow brightness characteristics, and in particular, can obtain phosphorescent particles with a large phosphorescent region per unit surface area. [Brief description of the drawings]

[0010] [Figure 1] 1a and 1b are enlarged micro-digital scope images showing the phosphorescent particles of Comparative Example 1 and the phosphorescent particles of Example 1, respectively, when irradiated with a predetermined light. [Diagram 2] 2a and 2b are SEM images showing the luminous particles of Example 2 and the luminous particles of Comparative Example 2, respectively. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The method for producing phosphorescent particles of the present invention includes the steps of: preparing a phosphorescent phosphor which is a strontium aluminate compound doped with a lanthanoid rare earth element as an activator (step 1); treating the surface of the phosphorescent phosphor with an organic acid (step 2); reducing the surface of the phosphorescent phosphor treated with the organic acid (step 3); and oxidizing the surface of the reduced phosphorescent phosphor (step 4). Next, each step will be described in detail.

[0012] [1st step] The first step is to prepare a phosphorescent phosphor, which is a strontium aluminate compound doped with a lanthanoid rare earth element as an activator. The phosphorescent phosphor is a strontium aluminate compound, especially SrAl2O4 or Sr4Al 14 O 25 The above-mentioned cathode is doped with a lanthanoid rare earth element (europium (Eu) and / or dysprosium (Dy)) as an activator, and in particular, those doped with Eu and Dy are preferred. Such a phosphorescent phosphor can be obtained by preparing spherical γ-Al2O3, SrCO3, Eu2O3, Dy2O3 and H3BO3 powders as raw material powders, weighing them so that the molar ratio of Al / (Sr+Eu+Dy) is within the range of 1.90-1.99 (preferably 1.97-1.99) and the amount of H3BO3 is within the range of 0.5% by weight to 2.5% by weight (preferably 2.0% by weight to 2.5% by weight), mixing the above powders, putting the resulting mixture into a crucible, and heating it at 1350-1450°C for 2-4 hours under a reducing atmosphere. The resulting lump is then pulverized by ball milling or the like, and the resulting pulverized product is screened to have a uniform particle size (preferably a particle size of about 60μm-100μm), making it into a form suitable for paints and the like. The phosphorescent phosphor obtained by this manufacturing process emits yellow-green to blue light in the dark when irradiated with light from a fluorescent lamp. The phosphorescent phosphor is not limited to the phosphor produced by the above manufacturing process, but may be a commercially available strontium aluminate phosphor or a phosphor produced by another manufacturing process.

[0013] [Second process] The second step is to treat the surface of the prepared phosphorescent phosphor with an organic acid. It is believed that by treating the phosphorescent phosphor, which is a strontium aluminate compound, with an organic acid, the organic acid modifies at least the metal in the heterogeneous phase region on the surface of the phosphorescent phosphor that is not involved in phosphorescence. Preferred examples of the organic acid include organic acids having a carbon number of 8 or less. Specific examples include citric acid, formic acid, acetic acid, and lactic acid. Such a step can be carried out, for example, by dispersing a prepared phosphorescent phosphor in ion-exchanged water and adding an organic acid. That is, a first dispersion liquid is prepared in which a phosphorescent phosphor treated with an organic acid is dispersed. The phosphorescent phosphor in the first dispersion liquid is preferably 1% by weight to 20% by weight, particularly 5% by weight to 15% by weight. The pH of the first dispersion liquid at room temperature is preferably 3 to 6, more preferably 4 to 6. After the organic acid is added, the first dispersion liquid is preferably stirred for 10 to 40 minutes, particularly 20 to 30 minutes.

[0014] [3rd step] The third step is to reduce the surface of the phosphorescent material that has been treated with an organic acid. It is believed that the metal ions on the surface of the phosphorescent material that has been modified with an organic acid are reduced. Such a step can be carried out, for example, by adding a reducing agent to the first dispersion liquid prepared in the second step. The reducing agent is not particularly limited, but examples thereof include sodium borohydride, hydrazine, diisobutylaluminum hydride, etc. In particular, when the reducing agent is sodium borohydride, it is preferable to neutralize the first dispersion liquid prepared in the second step by passing it through a cation exchange resin and then add it. In this case, it is preferable to add a sodium borohydride solution obtained by adding sodium borohydride to ion-exchanged water to the neutralized first dispersion liquid. The amount of sodium borohydride added is, for example, 0.001% by weight to 0.05% by weight, preferably 0.02% by weight or less, and particularly preferably 0.01% by weight or less.

[0015] [4th step] The fourth step is a step of oxidizing the surface of the reduced phosphorescent phosphor. More specifically, this is a step of separating the phosphorescent phosphor from the dispersion liquid to which the reducing agent of the third step has been added, and subjecting the surface of the phosphorescent phosphor to an oxidation treatment. The oxidation treatment of the surface of the phosphorescent phosphor is not particularly limited. In this process, the phosphorescent phosphor is separated from the dispersion liquid to which the reducing agent has been added in the third process, and a second dispersion liquid (pH 7) is prepared by dispersing the phosphorescent phosphor again in ion-exchanged water. It is preferable to oxidize the phosphorescent phosphor by the dissolved oxygen in the second dispersion liquid. It is particularly preferable to oxidize the phosphorescent phosphor by the dissolved oxygen at a liquid temperature of 40°C or higher, particularly 45°C or higher. For example, the dispersion liquid dispersed in ion-exchanged water is heated with stirring, and maintained for 10 to 30 minutes, whereby the phosphorescent phosphor can be preferably oxidized. An oxidizing agent may be added to the second dispersion liquid. The oxidizing agent is not particularly limited, but may be sodium hypochlorite or the like.

[0016] By recrystallizing the surface of the phosphorescent phosphor in this way, the afterglow luminance characteristics can be improved. In other words, by recrystallizing the heterogeneous phases present on the surface of the phosphorescent phosphor by surface treatment, the heterogeneous phases that are not involved in the phosphorescence are reduced, and the Eu 2+ →Eu 3+ This is thought to be because the charge transfer to the

[0017] After the phosphorescent particles are manufactured by the manufacturing method of the present invention, a water-resistant coating may be provided on the surface of the phosphorescent particles. Such a coating is not particularly limited, but for example, a composite oxide having a skeleton (siloxane bond) in which a plurality of silicon atoms are bonded via oxygen atoms is preferably used. Particularly preferred examples of such a composite oxide include a composite oxide obtained by hydrolysis and condensation of alkoxysilane, and a composite oxide (inorganic composite oxide) formed by mixing an acidic solution containing aluminum ions and silicate ions with a basic solution containing an alkali metal silicate. EXAMPLES

[0018] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples.

[0019] [Example 1] As the phosphorescent phosphor, Eu and Dy doped strontium aluminate phosphorescent particles (product name: GDk130100WP (water-resistant treated product), average particle size 100μ, manufactured by LTI Corporation (hereinafter, LTI phosphorescent phosphor) were prepared. 100 g of ion-exchanged water was placed in a beaker, 10 g of LTI-manufactured phosphorescent phosphor was dispersed therein, and 10% citric acid solution (1 ml) was added so that the pH of the dispersion became 5.0. The treated solution was then neutralized by passing it through a cation exchange resin, and 0.5 g of a 1% by weight solution of sodium borohydride in ion-exchanged water was added. After the reduction, 3 g of amphoteric ion exchange resin was added to trap the sodium borohydride, and the amphoteric ion exchange resin was separated from the treatment solution using a 300 μm mesh, and then the phosphorescent phosphor was separated. Again, ion-exchanged water was added so that the phosphorescent phosphor concentration was 10% by weight, and the liquid temperature was kept at 50°C while stirring for 30 minutes to produce phosphorescent particles in which the particle surfaces of the phosphorescent phosphor were oxidized by dissolved oxygen. This is Example 1.

[0020] [Example 2] Ion exchange water was added so that the phosphorescent particles of Example 1 were 10% by weight. 1g of an acidic solution (RE015-5A manufactured by Kato Chemical Industry Co., Ltd.) with a pH of 4.2 containing aluminum phosphate, ethyl silicate, ammonia and hydrochloric acid, and 1g of a basic solution (potassium phosphate-based water glass, solid content 5%) (PK09-5B manufactured by Kato Chemical Industry Co., Ltd.) with a pH of 12 containing potassium phosphate were added successively to the solution so that the pH was 10, and phosphorescent particles coated with a composite oxide were produced. These phosphorescent particles are Example 2. The phosphorescent particles of Example 2 are the phosphorescent particles of Example 1 to which a composite oxide having a siloxane bond is provided to impart water resistance.

[0021] [Example 3] As the phosphorescent phosphor, an LTI manufactured phosphorescent phosphor (product name: GDk130100WP (water-resistant product) manufactured by LTI Corporation, average particle size 100μ) was prepared. 100 g of ion-exchanged water was placed in a beaker, 10 g of LTI's phosphorescent phosphor was dispersed therein, and 10% formic acid solution (8 ml) was added so that the pH of the dispersion became 5.0. The treated solution was then neutralized by passing it through a cation exchange resin, and 0.5 g of a 1% by weight solution of sodium borohydride in ion-exchanged water was added. After the reduction, 3 g of amphoteric ion exchange resin was added to trap the sodium borohydride, and the amphoteric ion exchange resin was separated from the treatment solution using a 300μ mesh, and then the phosphorescent phosphor was separated. Again, ion-exchanged water was added to the solution so that the phosphorescent phosphor was 10% by weight, and 1g of an acidic solution (RE015-5A manufactured by Kato Chemical Industry Co., Ltd.) with a pH of 4.2 containing aluminum diphosphate, ethyl silicate, ammonia, and hydrochloric acid, and 1g of a basic solution (potassium phosphate-based water glass, solid content 5%) (PK09-5B manufactured by Kato Chemical Industry Co., Ltd.) with a pH of 12 containing potassium phosphate were added successively to the solution so that the pH was 10, producing phosphorescent particles in which the surface of the phosphorescent phosphor was coated with a composite oxide. These phosphorescent particles are referred to as Example 3.

[0022] [Comparative Example 1] A phosphorescent phosphor manufactured by LTI (product name: GDk130100WP (water-resistant treated product), average particle size 100μ, manufactured by LTI Corporation) was prepared and used as Comparative Example 1.

[0023] [Comparative Example 2] As the phosphorescent phosphor, an LTI manufactured phosphorescent phosphor (product name: GDk130100WP (water-resistant product) manufactured by LTI Corporation, average particle size 100μ) was prepared. To a solution of this LTI phosphorescent phosphorescent material at 10% by weight, ion-exchanged water was added, and 1g of an acidic solution (RE015-5A, manufactured by Kato Chemical Industry Co., Ltd.) with a pH of 4.2 containing aluminum phosphate, ethyl silicate, ammonia, and hydrochloric acid, and 1g of a basic solution (potassium phosphate-based water glass, solid content 5%) (PK09-5B, manufactured by Kato Chemical Industry Co., Ltd.) with a pH of 12 containing potassium phosphate were added successively to the solution to adjust the pH to 10, producing phosphorescent particles with a composite oxide coating on the surface. These phosphorescent particles are referred to as Comparative Example 1.

[0024] "Measurement of afterglow luminance characteristics" The phosphorescent particles of Examples 1, 2, and 3 and the phosphorescent particles of Comparative Examples 1 and 2 were placed in a 5 mm thick case and irradiated with a 200 Lux D65 light source for 20 minutes. The luminance was measured after 2 minutes and 20 minutes using a color luminance meter (BM-5AS manufactured by Topcon Technohouse Corporation). The results are shown in Table 1.

[0025] [Table 1]

[0026] The phosphorescent particles of Examples 2 and 3 were the phosphorescent particles of Example 1 with a coating of a silicon oxide composite oxide, but even with such a coating, they showed similar afterglow brightness characteristics. In other words, the coating did not impede the surface treatment that is a feature of the present invention, and rather, it was found that the coating improved the brightness after 2 minutes. Comparing the phosphorescent particles of Example 1 and the phosphorescent particles of Comparative Example 1, no significant difference in luminance was observed after 20 minutes, but the phosphorescent particles of Example 1 had a luminance of 2000 mcd / m after 2 minutes. 2 In addition, when comparing the phosphorescent particles of Example 2, which were coated with an inorganic composite oxide, with the phosphorescent particles of Comparative Example 2, the phosphorescent particles of Example 2 had a luminance of 1500 mcd / m2 after 2 minutes. 2 Furthermore, when comparing the phosphorescent particles of Example 3, which used formic acid as the organic acid, with the phosphorescent particles of Comparative Example 2, the phosphorescent particles of Example 3 had a luminance of 1000mc / m 2 It has gotten even bigger. It was found that the initial afterglow luminance (luminance after 2 minutes) was greatly improved by carrying out the surface treatment that is a feature of the present invention.

[0027] Next, a 3W UV light was applied to observe the phosphorescent particles of Example 1 and the phosphorescent particles of Comparative Example 1 at 150x magnification using a digital microscope (VHX8000, manufactured by Keyence Corporation). The images are shown in Figures 1a and 1b, respectively. On the surface of the phosphorescent particles of Comparative Example 1 (Fig. 1a), large non-glowing areas were observed. In contrast, the phosphorescent particles of Example 1 (Fig. 1b) had several non-glowing dots, but it was clear that the particles were luminous overall. Thus, it was found that the afterglow luminance characteristics (particularly the initial afterglow luminance) were improved by carrying out the surface treatment that is a feature of the present invention.

[0028] Next, Figures 2a and 2b are 5000x SEM images of the luminous particles of Example 2 and Comparative Example 2, respectively, coated with a composite oxide. Multiple cracks were observed in the luminous particles of Comparative Example 2, which were not surface-treated. It was found that the composite oxide could be stably coated on the luminous particles by performing the surface treatment in this way.

Claims

1. A step of preparing a phosphorescent phosphor which is a strontium aluminate compound doped with a lanthanide rare earth element as an activator; a step of treating a surface of the phosphorescent phosphor with an organic acid; reducing the surface of the phosphorescent phosphor treated with the organic acid; and oxidizing the surface of the reduced phosphorescent phosphor. A method for producing phosphorescent particles.

2. The organic acid has 8 or less carbon atoms. A method for producing the phosphorescent particles according to claim 1.

3. The method further comprises the step of providing a water-resistant coating on the surface of the oxidized phosphorescent phosphor. A method for producing the phosphorescent particles according to claim 1 or 2.

Citation Information

Patent Citations

  • Coating agent for fluorescent substance, fluorescent powder given by using the same, and method for producing the same

    JP2003089767A

  • Method for producing photoluminescent phosphor

    JP2007077214A

  • High-luminance emission particle and method for producing the same

    JP2007145991A

  • Persistent phosphorescent composite material

    JP2014095077A

  • Hard copying machine

    JP1984067787A